2021
DOI: 10.3390/app11073246
|View full text |Cite
|
Sign up to set email alerts
|

Computationally Efficient PM Power Loss Mapping for PWM Drive Surface-Mounted Permanent Magnet Synchronous Machines

Abstract: This paper proposes a computationally efficient approach for mapping permanent magnet (PM) power loss in permanent magnet synchronous machines (PMSMs). The PM loss mapping method here uses time-step finite element analysis (FEA) to determine the function parameters representing the loss variation with speed (frequency), amplitude modulation ratio, carrier ratio, and stator current and is suitable for rapid evaluation of machine performance over the entire torque–speed envelope. The PM loss can be accurately ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…In [20], Guohui Yang et al focused on the influence of stator slot opening of permanent magnet synchronous motor on the loss of permanent magnets. Reference [21] proposes a new calculation method for power loss of permanent magnet based on a two-dimensional finite element and fitting method which can achieve the balance of rapidity and accuracy of calculation of permanent magnet loss with sinusoidal input. In general, the rotor loss in PMSM mainly includes rotor core loss and permanent magnet loss which are caused by the air gap permeability, the space harmonic, and the time harmonic caused by the stator current.…”
Section: Rotor Core Magnetic Field Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In [20], Guohui Yang et al focused on the influence of stator slot opening of permanent magnet synchronous motor on the loss of permanent magnets. Reference [21] proposes a new calculation method for power loss of permanent magnet based on a two-dimensional finite element and fitting method which can achieve the balance of rapidity and accuracy of calculation of permanent magnet loss with sinusoidal input. In general, the rotor loss in PMSM mainly includes rotor core loss and permanent magnet loss which are caused by the air gap permeability, the space harmonic, and the time harmonic caused by the stator current.…”
Section: Rotor Core Magnetic Field Analysismentioning
confidence: 99%
“…In [20], Guohui Yang et al focused on the influence of stator slot opening of permanent magnet synchronous motor on the loss of permanent magnets. Reference [21] proposes a new calculation method for power loss of permanent magnet based on a twodimensional finite element and fitting method which can achieve the balance of rapidity and accuracy of calculation of permanent magnet loss with sinusoidal input.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, consideration of the PM loss without investigation of hysteresis loss is not accurate. The loss mapping technique is a type of the analytical modelling to the PM losses [129,130,139]. It is fast, but limited to a type of the magnet, shape of the rotor, and shape of the stator.…”
Section: Permanent Magnet Lossesmentioning
confidence: 99%
“…In these models, the eddy current loss is the only investigated portion of the PM loss and the hysteresis PM loss is ignored [22]. It was shown that the hysteresis losses are approximately two times of the eddy current losses in PMs [139]. Therefore, consideration of the PM loss without investigation of hysteresis…”
Section: Mechanical Lossesmentioning
confidence: 99%
“…A power system's safe operation determines whether human activities are carried out normally, so the reliability of a power system is a very relevant issue for people today [1][2][3]. At the heart of the power industry's energy supply are large-scale synchronous machines, of which regular operation determines whether a power system is adequately supplied with energy [4,5]. As a critical component of a synchronous machine, winding may cause defects, such as winding turn-to-turn faults and grounding short-circuits during synchronous machine operation [6].…”
Section: Introductionmentioning
confidence: 99%